2010
DOI: 10.1097/yct.0b013e3181b00f32
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Response to Electroconvulsive Therapy Obtained Using the Three-Factor Structure of the Montgomery and Åsberg Depression Rating Scale for Treatment-Resistant Depressed Patients

Abstract: This study suggests that a high factor 1 MADRS score at pretreatment was a good predictor of response to ECT in patients with treatment-resistant MDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…The remaining 1118 citations were screened on the basis of title and abstract; 1085 citations were excluded at this stage. Full‐text review was conducted on the 33 remaining citations, with 14 excluded at this stage: Eight studies did not have head to head comparisons of patients with BDD and/or MDD , three studies did not have measures of ECT efficacy , one study was a letter to the editor citing other included studies , and one study did not define response or remission criteria . Ultimately, 19 studies met our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 1118 citations were screened on the basis of title and abstract; 1085 citations were excluded at this stage. Full‐text review was conducted on the 33 remaining citations, with 14 excluded at this stage: Eight studies did not have head to head comparisons of patients with BDD and/or MDD , three studies did not have measures of ECT efficacy , one study was a letter to the editor citing other included studies , and one study did not define response or remission criteria . Ultimately, 19 studies met our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…133 One study reported that ECT responders displayed higher scores on a MADRS dysphoria factor compared to nonresponders, while the procedure had only a small effect on a MADRS vegetative factor. 143 Although relatively large trials have been conducted in the NIN field, 29,31,144 to the best of our knowledge, there is no published research using machine-learning algorithms to predict NIN response based on a clinical dataset -as has already been done in pharmacological trials. 145 For example, using a gradient boosting model, Chekroud et al 145 identified in STAR*D a dataset of 25 variables that predicted depression response significantly above chance.…”
Section: Convulsive Modalitiesmentioning
confidence: 99%
“…Our recent preliminary research suggested that a higher score on factor 1 was a good predictor of response to ECT in patients with treatment-resistant depression 6. We recruited a further group of old patients and reanalyzed the effects of differences in response to ECT in old patients with treatment-resistant depression (n = 18) by using the three-factor MADRS structure proposed by Suzuki et al5…”
Section: Introductionmentioning
confidence: 99%